REDUCTION OF CHLORIDE ION INGRESS INTO REINFORCED CONCRETE USING A HYDROPHOBIC ADDITIVE MATERIAL (Jurnal Teknologi (Sciences & Engineering), 2017)
Reinforced concrete structures located in areas near the coast are exposed to potential corrosion attack. Corrosion attack can occur because of the infiltration of chloride ions into concrete. At the initiation of the corrosion process, the load-carrying capacity of a reinforced concrete member will be affected negatively as a function of time. Infiltration of chloride ions into the concrete could be avoided by improving the micro-concrete properties. Enhancement of these properties can be achieved by use of an additive in the concrete. Calcium stearate is a hydrophobic material that can improve the properties of concrete. To determine the optimum contribution in concrete, laboratory experiments were conducted. Calcium stearate was added in varying contents of 0, 0.2, 0.9, and 1.9% of the cement weight. Four types of tests were performed to analyse the contribution of calcium stearate, namely the compressive strength test, absorption test, chloride ion infiltration test, and corrosion test. The results show that an optimum value of the compressive strength of concrete is obtained through the addition of calcium stearate. Besides that, the absorption, chloride ion infiltration, and corrosion value decrease significantly when a higher amount of calcium stearate is added to the concrete.Â Â